2002
DOI: 10.1177/152660280200900206
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Endoleak with Enhanced Ultrasound Imaging: Comparison with Biphasic Computed Tomography

Abstract: Ultrasound scanning with or without contrast enhancement was not as reliable as CT in diagnosing type II endoleak. CT imaging remains our surveillance modality of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 19 publications
2
62
0
Order By: Relevance
“…However, the majority of reports on DU performance to detect endoleaks after endovascular repair of abdominal aortic aneurysm [26][27][28][29][30][31] found inferior sensitivity and specificity compared to CT angiography. Nevertheless, contrast agents (Levovist) seem to increase the sensitivity of this color-flow DU, but with the risk of more false-positive results [32]. However, CT angiography carries some disadvantages, such as increased radiation exposure, potential contrast allergy and worsening of renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of reports on DU performance to detect endoleaks after endovascular repair of abdominal aortic aneurysm [26][27][28][29][30][31] found inferior sensitivity and specificity compared to CT angiography. Nevertheless, contrast agents (Levovist) seem to increase the sensitivity of this color-flow DU, but with the risk of more false-positive results [32]. However, CT angiography carries some disadvantages, such as increased radiation exposure, potential contrast allergy and worsening of renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is considered to be more accurate than ultrasound without contrast, and similar to magnetic resonance imaging (MR) and CT (Cantisani et al, 2011;Iezzi et al, 2009;Mirza et al, 2010;Sun 2006). McWilliams et al (2002) investigated 53 patients and found contrast enhanced ultrasound to be more sensitive than unenhanced ultrasound in detection of endoleak when compared to CT, but concluded that ultrasound (with or without contrast) was less reliable than CT. On the contrary, several other authors have concluded that contrast enhanced ultrasound may perform better than CT in detection of endoleak (Carrafiello et al, 2006;Clevert et al, 2008;Henao et al, 2006;Ten Bosch et al, 2010). Bakken & Illig (2010) presented a review summarizing use of ultrasound for detection of endoleak.…”
Section: Ultrasound In Post-operative Surveillancementioning
confidence: 99%
“…Sonographic contrast agents enhance the capability of color duplex imaging to detect endoleaks (McWilliams et al, 2002;Napoli et al, 2004). Are typically microbubbles of a perfluorocarbon gas encapsulated within a thin lipid or human albumin shell for stability while circulating in the blood pool.…”
Section: Sonographic Constrast Agentsmentioning
confidence: 99%